2007
DOI: 10.1161/01.res.0000265844.56493.ac
|View full text |Cite
|
Sign up to set email alerts
|

The BTB-Kelch Protein KLEIP Controls Endothelial Migration and Sprouting Angiogenesis

Abstract: Abstract-Sprouting and invasive migration of endothelial cells are important steps of the angiogenic cascade. Vascular endothelial growth factor (VEGF) induces angiogenesis by activating intracellular signal transduction cascades, which regulate endothelial cell morphology and function. BTB-kelch proteins are intracellular proteins that control cellular architecture and cellular functions. The BTB-kelch protein KLEIP has been characterized as an actin-binding protein that interacts with the nucleotide exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…Human umbilical vein endothelial cells (HUVECs) were isolated as described previously (38). HUVECs and bovine aortic endothelial cells (BAECs) (39) were cultivated in endothelial cell growth medium (ECGM, PromoCell) containing supplements, 10% FCS (Biochrom), and antibiotics. The following antibodies were used: goat anti-actin (I-19) (Santa Cruz Biotechnology), rabbit anti-Akt (Cell Signaling), mouse anti-pAkt (S473) (587F11) (Cell Signaling), rabbit anti-Dock180 (H-70) (Santa Cruz Biotechnology), goat anti-Elmo1 (Everest Biotech), mouse anti-Rac1 (Transduction Laboratories), mouse antipERK (E-4) (Santa Cruz Biotechnology), rabbit anti-ERK1 (K-23) (Santa Cruz Biotechnology), mouse anti human [pSer 139 ]Histone H2AX (9F3) (Enzo Life Science), Cy3-conjugated secondary antibodies (Dianova), and HRP-conjugated antibodies (DAKO).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human umbilical vein endothelial cells (HUVECs) were isolated as described previously (38). HUVECs and bovine aortic endothelial cells (BAECs) (39) were cultivated in endothelial cell growth medium (ECGM, PromoCell) containing supplements, 10% FCS (Biochrom), and antibiotics. The following antibodies were used: goat anti-actin (I-19) (Santa Cruz Biotechnology), rabbit anti-Akt (Cell Signaling), mouse anti-pAkt (S473) (587F11) (Cell Signaling), rabbit anti-Dock180 (H-70) (Santa Cruz Biotechnology), goat anti-Elmo1 (Everest Biotech), mouse anti-Rac1 (Transduction Laboratories), mouse antipERK (E-4) (Santa Cruz Biotechnology), rabbit anti-ERK1 (K-23) (Santa Cruz Biotechnology), mouse anti human [pSer 139 ]Histone H2AX (9F3) (Enzo Life Science), Cy3-conjugated secondary antibodies (Dianova), and HRP-conjugated antibodies (DAKO).…”
Section: Methodsmentioning
confidence: 99%
“…The assay was performed as previously described (39). The spheroids were stimulated upon embedding in collagen with 25 ng/ml VEGF for 24 h. The cumulative sprouting length was set in relation to control and is displayed in percent.…”
Section: Methodsmentioning
confidence: 99%
“…Endothelial behavior was analyzed as described (33). Apoptosis was determined using the Caspase-Glo 3/7 Assay (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…VEGF is a growth factor inducing several angiogenesis-related endothelial functions, including migration and proliferation (6). VEGF-receptor activation triggers several downstream signaling cascades, such as the extracellular signal-regulated kinase (ERK) 1/2 pathway (14), the serine/threonine kinase Akt with subsequent nitric oxide release (4,12,13), and the small GTPases Rho (19,27). Recent studies have suggested that VEGF-driven endothelial migration and angiogenesis require activation of the monomeric GTPase RhoA (19,27) and that inhibition of RhoA disrupts tube formation in threedimensional matrixes (8,16,22).…”
mentioning
confidence: 99%
“…VEGF-receptor activation triggers several downstream signaling cascades, such as the extracellular signal-regulated kinase (ERK) 1/2 pathway (14), the serine/threonine kinase Akt with subsequent nitric oxide release (4,12,13), and the small GTPases Rho (19,27). Recent studies have suggested that VEGF-driven endothelial migration and angiogenesis require activation of the monomeric GTPase RhoA (19,27) and that inhibition of RhoA disrupts tube formation in threedimensional matrixes (8,16,22). Molecularly, GTP-bound RhoA activates the serine/threonine kinases ROCK I and ROCK II (7,11), which in turn promote stabilization of F-actin, phosphorylation of regulatory myosin light chain and an increase in contractility, processes involved in cell migration and metastasis (2,21).…”
mentioning
confidence: 99%